ANALYSIS OF THE PHYSICAL PLAFON PLACES BASED PAPER BREEDING - Ety Jumiati; Sri Wahyuni Ritonga; Abdul Halim Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2020)
A pulp-based ceiling board has been made. Variations in the composition of mixing cement and pulp used include: 70%: 30%, 60%: 40%, and 50%: 50% and Variations in the composition of mixing cement, sand and pulp used include: 50%:20%:30%, 40%:20%:40%, 30%:20%:50% with FAS 0,4 and the printing and pressing time is 24 hours. The parameters of the test include: water absorption and density. Analysis of the ceiling board physical produced in sample A with a composition of 70%: 30% has a water absorption value = 19% and density = 1.58%, in sample B with a composition of 6%: 40% has a water absorption value = 26 , 8% and density = 1.53%, in sample C with a composition of 50%: 50% has a water absorption value = 26.05% and density = 1.45%, in sample D with a composition of 50%:20%:30% has a water absorption value = 24,3% and density = 1.67%, in sample E with a composition of 40%:20%:40% has a water absorption value = 20,9% and density = 1.45%, in sample F with a composition of 30%:20%:50% has a water absorption value = 14,8 % and density = 1.34%.